Early Outcome of Neonates Admitted with Meconium Aspiration Syndrome - Bhandari, Isha; Karmacharya Malla, Kalpana; Chaudhary, Brajesh Raj; Ghimire, Pukar (Journal of Nepal Health Research Council, 2023)
Background: Meconium aspiration syndrome is one of the commonest cause of respiratory distress in neonates. The incidence is still high in developing world. This study aims to study the clinical characteristics and early outcome of neonates admitted for meconium aspiration syndrome. Methods: This was a cross-sectional descriptive study done among neonates admitted to the neonatal Intensive Care Unit with a diagnosis of Meconium Aspiration syndrome. Relevant epidemiological, clinical and laboratory data were obtained. The early outcome of those neonate was studied. Results: Out of 140 neonates with a mean birth weight of 2865 + 543 grams,73.6% were male, of which 76.4% were referred cases while 23.6% were inborn. Of them 69.3% had history of thin type of meconium while 30.7% had thick type of meconium during delivery. Of all mothers, 74.3% were primigravida, 4.3% had intrapartum fever of unknown source,11.4% suffered from urinary tract infection while 2.8% had hypertension. Premature rupture of membrane had occurred among 7.9% and oligohydramnios was found in 10%. Half of them (50.7%) had spontaneous vaginal delivery, 44.3% had caesarian section, while 4.8% had assisted delivery. Around one third of the neonates (37.1%) were given supplemental oxygen via nasal prongs, 25.7% via head box, 27.1% via continuous positive airway pressure and 10% intubated. Around half of the neonates (42.1%) had no complications. Complication noted were sepsis, birth asphyxia, seizures and polycythemia in 35%, 14.3%, 5.7% and 2.9% respectively. Mortality occurred among 5.0% of them. Conclusions: Meconium aspiration syndrome is one of the commonest cause of respiratory distress in a neonate which is associated with common maternal risk factors especially in primigravida which included Urinary tract infection, hypertension and oligohydramnios. Keywords: Meconium; meconium aspiration syndrome; newborn